2023
DOI: 10.1055/s-0043-1769014
|View full text |Cite
|
Sign up to set email alerts
|

Increased Levels of Inflammatory and Endothelial Biomarkers in Blood of Long COVID Patients Point to Thrombotic Endothelialitis

Abstract: The prevailing hypotheses for the persistent symptoms of Long COVID have been narrowed down to immune dysregulation and autoantibodies, widespread organ damage, viral persistence, and fibrinaloid microclots (entrapping numerous inflammatory molecules) together with platelet hyperactivation. Here we demonstrate significantly increased concentrations of von Willebrand factor (VWF), platelet factor 4 (PF4), serum amyloid A (SAA), α-2 antiplasmin (α-2AP), endothelial-leukocyte adhesion molecule 1 (E-selectin), and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
17
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 16 publications
(21 citation statements)
references
References 22 publications
0
17
0
Order By: Relevance
“…In addition, previous studies have reported elevated levels of biomarkers such as vascular endothelial growth factor (VEGF), von Willebrand factor (VWF), platelet factor 4 (PF4), serum amyloid A (SAA), α-2 antiplasmin (α-2AP), endothelial-leukocyte adhesion molecule 1 (E-selectin), soluble CD40 ligand (sCD40L) and platelet endothelial cell adhesion molecule (PECAM-1) related to clotting and endothelial dysfunction in Long COVID patients, suggesting thrombotic endothelialitis as a central pathology of the condition 40 . Further studies are necessary to assess levels of these and other markers to determine whether they correlate with microclot counts.…”
Section: Discussionmentioning
confidence: 99%
“…In addition, previous studies have reported elevated levels of biomarkers such as vascular endothelial growth factor (VEGF), von Willebrand factor (VWF), platelet factor 4 (PF4), serum amyloid A (SAA), α-2 antiplasmin (α-2AP), endothelial-leukocyte adhesion molecule 1 (E-selectin), soluble CD40 ligand (sCD40L) and platelet endothelial cell adhesion molecule (PECAM-1) related to clotting and endothelial dysfunction in Long COVID patients, suggesting thrombotic endothelialitis as a central pathology of the condition 40 . Further studies are necessary to assess levels of these and other markers to determine whether they correlate with microclot counts.…”
Section: Discussionmentioning
confidence: 99%
“…The same is true in myalgic encephalitis/chronic fatigue syndrome 61 and long COVID. 62 Consequently, the presence of a soup of inflammatory molecules in circulation that individually might bind to the numerous receptors on platelets, and have direct protein–protein interactions, may therefore be a crucial predictor of the detailed effects of any systemic inflammation. These interactions should be seen as central to the cause and effect of disease development and presentation of both diverse and overlapping symptoms.…”
Section: Variations In Patterns Of Cytokinesmentioning
confidence: 99%
“…One thing we do know, however, is that microclots covary with (and in our view are thus largely responsible for) the severity of disease in both acute and long COVID 67 and in fact contribute to widespread thrombotic endothelialitis in long COVID. 62 …”
Section: Variation In Microclot Propertiesmentioning
confidence: 99%
“…Homo- and hetero-polymerisation and their catalysis are then referred to, respectively, as (self-)’seeding’ [140,152-166] and ‘cross-seeding’ [153,167-174]. More recently, we have established the prevalence of these fibrinaloid microclots in post-viral diseases such as Long COVID [106,175-178] (and see [179]) and ME/CFS (myalgic encephalopathy/chronic fatigue syndrome) [180,181]. The lower amyloidogenicity of omicron versus earlier variants of SARS-CoV-2 is also reflected in its lower virulence [182], implying that these microclots are on the aetiological pathway of the disease, and they can explain many symptoms [183], including fatigue [184], post-exertional symptom exacerbation [185], autoantibody generation [107] and Postural Orthostatic Tachycardia Syndrome (POTS) [186].…”
Section: Introductionmentioning
confidence: 99%